2012
DOI: 10.1002/pits.21664
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Teacher Treatment Integrity Through Performance Feedback Provided by School Personnel

Abstract: When implementing behavioral interventions in educational settings, some implementers need support to maintain high levels of treatment integrity. Performance feedback has a large body of research supporting it as a strategy for improving teachers’ implementation of classroom interventions. However, in most prior studies, performance feedback has been delivered by a researcher, not by a school staff member, which limits generalizability of results to applied settings. In this study, school personnel (i.e., int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 20 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Comprehensive training approaches are effective but resource-intensive (e.g., Martens, Hiralall, & Bradley, 1997; Myers, Simonsen, & Sugai, 2011; Sanetti, Fallon, & Collier-Meek, 2013; Simonsen, Myers, & DeLuca, 2010; Solomon, Klein, & Politylo, 2012). The field needs to identify similarly effective, but more efficient, approaches to supporting teachers’ classroom management.…”
mentioning
confidence: 99%
“…Comprehensive training approaches are effective but resource-intensive (e.g., Martens, Hiralall, & Bradley, 1997; Myers, Simonsen, & Sugai, 2011; Sanetti, Fallon, & Collier-Meek, 2013; Simonsen, Myers, & DeLuca, 2010; Solomon, Klein, & Politylo, 2012). The field needs to identify similarly effective, but more efficient, approaches to supporting teachers’ classroom management.…”
mentioning
confidence: 99%
“…Within consultation, it seems that implementation planning may be a more highly feasible strategy for supporting intervention implementation than performance feedback. It only required one 20-to 30-minute meeting and resulted in meaningful changes in both teacher behavior and student outcomes as compared to performance feedback that typically involves a regular review of treatment integrity data, as well as a brief (10 min) regular meetings (Noell, 2010;Sanetti, Fallon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a systematic review and a meta-analysis suggest that performance feedback can be considered an EBP for promoting treatment integrity (Fallon, Collier-Meek, Maggin, Sanetti, & Johnson, in press;Solomon, Klein, & Politylo, 2012). There is a significant limitation to the literature base, however, in that there has only been one evaluation in which school-based personnel (as opposed to researchers or outside consultants) were responsible for assessing treatment integrity and implementing performance feedback when appropriate (Sanetti, Fallon, & Collier-Meek, 2013). Results of this study demonstrated that school personnel could implement performance feedback, but that it was highly time intensive and the increases in teachers' adherence were variable.…”
mentioning
confidence: 88%
“…Traditional PD methods of increasing teachers' use of PBM include didactic instruction, coaching, modeling, role play, and performance feedback, and provide an intense focus on the knowledge and performance of specific PBM strategies (State, Simonsen, Hirn, & Wills, 2019). Performance feedback in particular has a large body of evidence showing its effectiveness in increasing teacher skill in PBM (Fallon, Collier‐Meek, Maggin, Sanetti, & Johnson, 2015); however, research is mixed on the degree to which these approaches produce enduring changes in teacher practice (Hagermoser Sanetti, Fallon, & Collier‐Meek, 2013; Simonsen et al, 2017). School‐based consultation studies have found that many teachers significantly decrease behavior intervention fidelity after outside support has ended (Noell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Stormont, Reinke, Newcomer, Marchese, and Lewis (2015) reviewed studies incorporating performance feedback for teacher use of PBM and found that only 28% collected follow up data. Additionally, a number of researchers have discussed the limitation of providing research‐based staff to implement PBM coaching and performance feedback, questioning the feasibility and sustainability of coaching when implemented by school‐based personnel (Gilmour, Wehby, & McGuire, 2017; Hagermoser Sanetti et al, 2013; Simonsen et al, 2014). These studies show that even with the best PD practices available, many teachers may fail to sustain PBM over time.…”
Section: Introductionmentioning
confidence: 99%